2014
DOI: 10.1038/ncomms4413
|View full text |Cite
|
Sign up to set email alerts
|

Astrocytic laminin regulates pericyte differentiation and maintains blood brain barrier integrity

Abstract: Blood brain barrier (BBB) breakdown is not only a consequence of, but also contributes to many neurological disorders, including stroke and Alzheimer’s disease. How the basement membrane (BM) contributes to the normal functioning of the BBB remains elusive. Here we use conditional knockout mice and an acute adenovirus-mediated knockdown model to show that lack of astrocytic laminin, a brain-specific BM component, induces BBB breakdown. Using functional blocking antibody and RNAi, we further demonstrate that as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
243
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 286 publications
(265 citation statements)
references
References 59 publications
9
243
0
Order By: Relevance
“…However, the extent of decrease in laminin is notably more pronounced than that of CD31. In addition to endothelial cells, specific subtypes of laminin are also produced by astrocytes and pericytes (Yao et al ., 2014). Previously, it has been shown that dysregulation in production of astrocytic laminin can compromise BBB by affecting pericyte differentiation and vascular smooth muscle cell function (Chen et al ., 2013; Yao et al ., 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the extent of decrease in laminin is notably more pronounced than that of CD31. In addition to endothelial cells, specific subtypes of laminin are also produced by astrocytes and pericytes (Yao et al ., 2014). Previously, it has been shown that dysregulation in production of astrocytic laminin can compromise BBB by affecting pericyte differentiation and vascular smooth muscle cell function (Chen et al ., 2013; Yao et al ., 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to endothelial cells, specific subtypes of laminin are also produced by astrocytes and pericytes (Yao et al ., 2014). Previously, it has been shown that dysregulation in production of astrocytic laminin can compromise BBB by affecting pericyte differentiation and vascular smooth muscle cell function (Chen et al ., 2013; Yao et al ., 2014). Recently, by employing a high‐resolution MRI method, blood to brain transfer of gadolinium bound to plasma proteins (shows entry of large molecules that cannot usually enter the brain) was measured regionally in a quantitative manner.…”
Section: Discussionmentioning
confidence: 99%
“…A conditional knock-out of ␤1-containing integrins in both pericytes and VSMCs using PDGFR␤-Cre resulted in decreased VSMC differentiation, providing further support for a role for laminin receptor interactions in promoting VSMC maturation (Abraham et al, 2008). However, a separate more recent study, using the mice that lack laminin expression selectively in astrocytes, reported increased levels of ␣-SMA immunoreactivity associated with the cerebral vasculature, suggesting that laminins can also suppress VSMC maturation (Yao et al, 2014). The mechanism by which laminins could either decrease or increase VSMC maturation remains unclear; however, these studies clearly highlight laminins as key regulators of VSMCs.…”
Section: Laminins Pericytes and Bbb Maturationmentioning
confidence: 97%
“…Initially, ultrastructural analysis in dy/dy mice (in which laminin ␣2 is deficient but not absent) revealed no obvious defects (Jucker et al, 1996). However, mutations in Lama2, which encodes laminin ␣2, or in genes that encode enzymes needed for dystroglycan post-translational modifications, cause congenital muscular dystrophies with accompanying brain abnormalities, including seizures, perturbed cortical development, and MRI white matter hypointensities (Miyagoe-Suzuki et al, 2000;Allamand and Guicheney, 2002;Moore et al, 2002;Buteicȃ et al, 2008;Yoshioka et al, 2008;Fujii et al, 2011), with MRI abnormalities hypothesized to reflect, at least in part, BBB defects (Caro et al, 1999). Recently, mice that lack laminin ␥1 expression selectively (removing laminins-111 and -211) in astrocytes were reported to have impaired VSMC function and hemorrhagic stroke .…”
Section: Introductionmentioning
confidence: 99%
“…EC-pericyte co-culture assays in vitro and quail chick chorioallantoic membrane (CAM) assays have provided evidence that pericytes help to maintain extracellularly deposited basement membrane proteins (Stratman and Davis, 2012;Stratman et al, 2009Stratman et al, , 2010Zhao et al, 2015). Although ECs appear to have the capacity to synthesize basement membrane proteins on their own, they do not appear to be properly deposited to form an EC-associated basement membrane in the absence of mural cells, or mural cells/astrocytes in the case of the BBB (Abraham et al, 2008;Armulik et al, 2010Armulik et al, , 2011bYao et al, 2014;Chen et al, 2013). Although these assays suggest that ECmural cell interactions are important for building and maintaining the vascular basement membrane, a full analysis of the requirement for both cell types in formation and stabilization of the basement membrane in the developing vasculature of an intact organism, in particular around larger-caliber vessels such as the dorsal aorta, has not been carried out.…”
Section: Introductionmentioning
confidence: 99%